Differential equation analysis in biomedical science and engineering : ordinary differential equation applications with R - Schiesser, W. E. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Features a solid foundation of mathematical and computational tools to formulate and solve real-world ODE problems across various fields With a step-by-step approach to solving ordinary differential equations (ODEs), Differential Equation Analysis in Biomedical Science and Engineering: Ordinary Differential Equation Applications with R successfully applies computational techniques for solving real-worldODE problems that are found in a variety of fields, including chemistry, physics, biology, and physiology. The book provides readers with the necessary knowledge to reprodu.
Introduction to ordinary differential equation analysis bioreactor dynamics -- Diabetes glucose tolerance test -- Apoptosis (programmed cell death) -- Dynamic neuron model -- Stem cell dfferentiation -- Acetylcholine neurocycle -- Tuberculosis with dfferential infectivity -- Corneal curvature -- Stiff ode integration.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biomedical engineering -- Mathematics; Biomathematics; Bioreactors -- Data processing; Differential equations; Biomedical Engineering; Computer Simulation; Biomathematics; Biomedical engineering -- Mathematics; Bioreactors -- Data processing; Differential equations; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biomathematics; Biomedical engineering -- Mathematics; Bioreactors -- Data processing; Differential equations; Electronic books